9 Monocyte chemoattractant protein-1 as a biomarker of vascular dysfunction in patients with type 2 diabetes. (22nd March 2023) - MacDonald, William; Casanova, Francesco; Gooding, Kim; Aizawa, Kuni; Shore, Angela; Khan, Faisel
Abstract : Endothelial dysfunction has been shown to be strongly associated with cardiovascular disease (CVD) outcomes. CVD risk in diabetes shows heterogeneity and new biomarkers are required to stratify CVD risk in these patients. This study analysed the association of Monocyte Chemoattractant Protein-1 (MCP-1) with measures of vascular function in 509 patients with type 2 diabetes mellitus (T2DM). Endothelial function was measured using laser Doppler imaging (LDI) and peripheral artery tonometry (PAT) (EndoPat). Arterial stiffness was measured using carotid to femoral pulse wave velocity (PWV) (SphygmoCor). Firstly, the study showed the negative association of MCP-1 with endothelium-dependent vasodilator responses to acetylcholine (R2=0.240, p=5.02*10-10) as measured by LDI. Secondly, the study showed the negative association of MCP-1 with reactive hyperaemia index (RHI) (R2=0.0716, p=0.0109) and Framingham RHI (R2=0.0987, p=0.0294) as measured by PAT. Thirdly, the study showed the positive association of MCP-1 with PWV (R2=0.387, p=0.0088). Framingham risk factors, diabetes duration, HbA1c and eGFR were controlled for. The study also showed the independent association of MCP-1 with CVD death (odds ratio (OR)=18.2, 95% confidence interval (CI) [1.46 - 631.0], p=0.0487) and all-cause mortality (OR=4.51, 95% CI [1.07 - 21.8], p=0.0462) in a three-year follow-up period. There was no significant improvement to area under receiver operating characteristic curve (AUROC) when MCP-1 was added into risk models. This study shows MCP-1 to be a good candidate as a biomarker of vascular dysfunction in T2DM. Further research in larger cohorts with longer follow-up periods should be conducted to determine its usefulness in improvement of risk models.